PENGATURAN PULAU-PULAU TERLUAR SEBAGAI BATAS WILAYAH NEGARA TERLUAR REPUBLIK INDONESIA - Redemtus D.P Pone; Yohanes Arman, Cristoforus Darwin Dadi Lado, Maria Brigita Patty (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Indonesia is an archipelagic country with more than 17,000 islands, including small islands in the outermost and outermost parts that connect the country with other countries. With the many small, remote islands in Indonesia, the country does not need to monitor its natural resources from outside. Protect Indonesia's natural resources from smuggling and theft by monitoring the country's borders. If Indonesia had small islands in its outer regions, it would theoretically be easier to police its borders and protect its natural resources from smuggling and theft. This can help Indonesia monitor its borders and protect its natural resources from theft and smuggling. Based on Presidential Regulation Number 78 of 2005, Indonesia has 92 small outer islands, most of which are uninhabited and border with more than 10 countries. Indonesia has a long coastline of 81,000 km2 because of its many islands. Small overseas islands actually help control smuggling and theft of the country's marine resources and territorial sovereignty. The problem that will be discussed is how international law is regulated in the outermost island areas, how are the outermost islands in Indonesia regulated. The method used in this research is in the legal discipline, so this research is part of library law research, namely by "how to research library materials or what is called normative legal research. The legal materials studied are in the form of the 1982 UNCLOS regulations and several regulations. in Indonesia which regulates the existence of the outermost islands in Indonesian territory.